Operative management of immune checkpoint colitis following in-transit melanoma: Case report - Childers, Betzaira G.; Donovan, Eileen; Lo, Winifred M.; Janowak, Lauren M.; Sussman, Jeffrey; Janowak, Christopher F. (Frontiers in Oncology, 2023)
Immune checkpoint inhibitors are increasingly used as a powerful anti-neoplastic therapies in the setting of melanoma. Colitis is a known complication of immune checkpoint inhibitors that if often medically managed. We present a patient with stage IV melanoma with demonstrated in-transit disease undergoing immune checkpoint inhibitor therapy. The patient subsequently developed recalcitrant severe colitis that necessitated operative intervention and bowel resection. The association of immune check point inhibitors and immune related adverse effects are discussed as well as treatments of advanced colitis, including the possibility of surgical management in the setting of severe colitis with complications.